The dominant pests (Coleoptera) of cereal crops, and population forecast for this - Fedorenko, A. (Quarantine and plant protection, 2024)
Goal. Create a forecast of the development of harmful organisms in cereal crops, to determine the economic feasibility of applying plant protection measures. Methods. Analysis of the phytosanitary state of cereal crops in Ukraine, where the main attention is paid to the dominant pest species. Analysis of the areas of distribution of these pests, population dynamics, their phenology and the state of populations in the context of natural and climatic zones (Steppe, Forest-steppe and Polissya). To assess the phytosanitary state of crops, and its dynamic changes, the following are used: — the results of phytosanitary monitoring of crops (according to generally accepted methods), which were carried out directly by the staff of the forecast laboratory of the Institute of Plant Protection of NAAS; — current reports of researchers from other laboratories of the Institute of Plant Protection of NAAS from the places of business trips; — materials of decadal reports of regional plant protection stations, as well as signaling and forecasting points; — information on the phytosanitary situation from regional state research stations and institutes of NAAS. Results. A study of the phytosanitary state of cereal crops on the territory of Ukraine was carried out, the dominant species of pests were identified, materials were prepared regarding the peculiarities of the phytosanitary state in the conditions of the year, and a long-term (annual) forecast of the development of pests for the next year was drawn up, based on the appropriate analysis of the data obtained. Conclusions. In recent years, climate change in Ukraine has manifested itself through an increase in the average annual temperature, and an increase in the sum of effective temperatures. A decrease in the zone of sufficient soil moisture was noted, its line shifted to the north. Under the influence of abiotic factors, pests constantly change the boundaries of their habitat and zones of damage, therefore reliable protection of crops is impossible without constant monitoring, constant clarification of the species composition of phytophages, and phytosanitary forecast. Improved methodological approaches for assessing the phytosanitary state of acrocyanoses and the promptness of obtaining relevant data will allow agricultural producers to make timely decisions on the economic feasibility of using certain plant protection products.